BIOCLIMATIC ZONING OF THE PANTANAL - Neto, João Batista Ferreira; Pereira, Gabriel; Helena Silva, Rosa; Rosa Oliveira , Maxwell; Alves Damasceno Júnior , Geraldo (Ra’e Ga: o Espaço Geográfico em Análise, 2024)
Human thermal perception, or thermal comfort, is a critical variable that directly influences the health, productivity, and well-being of populations. However, specific studies on thermal comfort in the Pantanal and its sub-regions are scarce. This study analyzes the distribution of thermal comfort classes in the Pantanal and its sub-regions using the Universal Thermal Climate Index (UTCI) for the period of 1979 to 2023. The main objective was to assess thermal discomfort in the region, identifying comfort classes and examining the influence of El Niño-Southern Oscillation (ENSO) events on this index. The analysis, based on reanalysis climatic data and statistical techniques, mapped the areas most susceptible to thermal stress. The central and southern regions of the Pantanal, such as Porto Murtinho, stood out as the most uncomfortable due to heat, while sub-regions in the north, such as Cáceres and Poconé, showed lower levels of thermal stress. Additionally, it was observed that the months of October and November present the highest UTCI values, indicating extreme thermal discomfort due to heat during the spring. Summer was identified as the most uncomfortable season in terms of heat, while winter showed moderate heat discomfort. The investigation of ENSO events revealed a tendency for greater thermal discomfort during La Niña years. It is concluded that there is a progressive increase in heat-related thermal discomfort in the Pantanal region, with a particularly pronounced trend in the spring.